Enhancing Worker Productivity through the S-O-R Theory in Human Resource Management - Nuryanti Taufik; Apip Supriadi; Gusti Tia Ardiani; Dwi Hastuti Lestari Komarlina (Jurnal Manajemen Teori dan Terapan)
Objective: This paper examines the influence of empowering leadership on positive worker behavior and work productivity in various organizational settings.